Pedagogical Paradigm in Arabic Textbooks: Comparative Study of Kunuz Ta’līm al-‘Arabiyyah and al-‘Arabiyyah Baina Yadaik - Aqmar, Nadila Nur Izatil; Maghfurin, Ahmad; Asyári, Hasyim (Study Program of Arabic Language Teaching, 2026)
This study aims to analyze and compare the pedagogical paradigms in two Arabic textbooks, namely Kunuz Ta’līm al-Lugah al-'Arabiyyah volume 1 and Al Arabiyyah Baina Yadaik volume 1, to understand the relationships among learning approaches, material design, activities, and evaluation systems. The difference between structural and communicative approaches is seen as a reflection of educational ideologies that shape the learning experience and the direction of language competence development. This study uses a qualitative method with a comparative content analysis approach. Data were obtained through documentation of learning objectives, material preparation, activities, and assessment systems. Data analysis uses the Philipp Mayring model through the stages of determining analysis units, compiling operational definitions, coding, categorization, and presenting data systematically. The results of this study show that Kunuz Ta’līm al-Lugah al-'Arabiyyah applies a structural approach that emphasizes grammatical mastery, mechanistic exercises, and precision-based evaluation. In contrast, Al Arabiyyah Baina Yadaik uses a communicative approach that emphasizes language use in social contexts through interactive activities, skill integration, and fluency-based assessments. This difference is consistent across aspects of the roles of teachers and students, the organization of materials, and the learning media. The study concludes that the two textbooks reflect harmony between the pedagogical paradigm and its implementation, and complement each other in developing linguistic and communicative competencies.